PREVALENSI DAN INTENSITAS EKTOPARASIT PADA IKAN MAS (Cyprinus carpio L.) DI KABUPATEN SIGI - Juwahir, Andi; Ya'la, Zakirah Raihani; Mangitung, Septina Fifi; Rusaini, Rusaini (AgriSains, 2016)
The current study was conducted to identify ectoparasites, infected organs, prevalence and intensity of ectoparasites in cultured common carp (Cyprinus carpio L.). Experimental animals were collected from ponds in 9 villages in 3 subdistricts in Sigi District. It was found that generally the common carp was infected by Dactylogyrus sp., Trichodina sp., Argulus sp., Epistylis sp., Chilodonella sp. and Ichthyophthirius multifilis. Infected organs consist of skin, fins and gills. The prevalence of ectoparasites per subdistrict was between 0.0 and 66.7 % and the intensity ranged from 0.0 to 3.0 individuals/fish.Â Key words: common carp, ectoparasites, prevalence, intensity.